Coping in Chronic Tinnitus Patients - Meijers, Sebastiaan M.; Lieftink, Arno F.; Stegeman, Inge; Smit, Adriana L. (Frontiers in Neurology, 2020)
background: Tinnitus is the perception of sound without an external stimulus. A large part of the adult population experiences this symptom but never seeks professional help, where others have devastating complaints in daily life. This suggests that the impact of tinnitus varies among patients and may be influenced by coping strategies and multiple psychological factors. Method: Cross- sectional study of patients visiting the tertiary tinnitus referral center of the University Medical Center Utrecht, the Netherlands. 321 consecutive chronic tinnitus patients were evaluated by the tinnitus care group Utrecht from 6-2007 till 11-2012 of which 308 patients were included. Patients completed two tinnitus distress questionnaires (THI, TQ), a coping questionnaire (CISS) as well as a psychopathological questionnaire (SCL-90-R). Results: Emotional-orientated coping and distraction-orientated coping strategies were significantly correlated with the experienced tinnitus burden. Also a significant negative correlation with task orientated coping was found. The effect size was small. Tinnitus distress also had a significant positive correlation with anxiety, agoraphobia, depression, insufficiency of handling, distrust & personal sensitivity, hostility and sleeping problems. Conclusion: Patients with higher tinnitus handicap scores demonstrated the use different coping strategies than the patients with lower distress scores. This insight in coping strategies in a group of patients with high tinnitus burden is useful for counseling patients. As tinnitus coping strategy might be related to the extent and success of habituation, this outcome could be of interest to optimize tinnitus treatments in the near future.